IgY against enterotoxigenic Escherichia coli administered by hydrogel-carbon nanotubes composites to prevent neonatal diarrhoea in experimentally challenged piglets - Alustiza, Fabrisio Eduardo (2016)
In previous studies, the applicability of polymeric hydrogels for the protection of egg yolk immunoglobulin (IgY) against simulated gastric conditions was established. Thereafter, the performance of the hydrogels was improved with the addition of chitosan wrapped carbon nanotubes and the in vitro toxicity for porcine intestinal cells of these nanocomposites was assessed. The objective of the present study was to evaluate in vivo the protective efficacy of the nanocomoposite matrix for IgY when the immunoglobulin is used against enterotoxigenic Escherichia coli (ETEC) in challenged piglets. Groups of piglets orally challenged with 1011 CFU/mL of ETEC were treated with non-protected and protected IgY. The clinical response of each group was monitored and evaluated in terms of dehydration, rectal temperature, faecal consistency score and body weight gain. Blood parameters and histological aspects were also studied. The results showed that treatment of infected piglets with protected IgY reduced significantly the severity of diarrhea. Non-protected IgY group show a lower recovery rate. Blood parameters and histological aspects were normal in both groups. Collectively, these results support previous in vitro studies showing that the nanocomposites can be an effective method of IgY protection against gastric inactivation.